2010
DOI: 10.1074/jbc.m110.103408
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Receptor 4 Is a Cell Surface Receptor for Extracellular Ubiquitin

Abstract: Ubiquitin is one of the most highly conserved proteins in eukaryotes and plays major biological roles as a post-translational protein modifier. Ubiquitin is also a natural constituent of plasma, and several lines of evidence suggest that extracellular ubiquitin is an immune modulator with anti-inflammatory properties. In addition, ubiquitin treatment has been shown to limit inflammation and reduce organ injury in various disease models and species in vivo. However, its mechanism of action is unknown. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
210
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(223 citation statements)
references
References 50 publications
9
210
3
1
Order By: Relevance
“…Then, we investigated the inhibitory activity of CSB6B on the ubiquitin-protein interaction by examining the binding affinity of ubiquitin to CXCR4, a cell surface receptor that recognizes ubiquitin as a ligand [13][14][15]. Since ubiquitin binding to the cell surface would be mediated by CXCR4, the interaction of FITC-labeled ubiquitin with CXCR4 was assessed by measuring the fluorescence associated with human monocyte cells (THP-1) after treating CSB6B at various concentrations (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we investigated the inhibitory activity of CSB6B on the ubiquitin-protein interaction by examining the binding affinity of ubiquitin to CXCR4, a cell surface receptor that recognizes ubiquitin as a ligand [13][14][15]. Since ubiquitin binding to the cell surface would be mediated by CXCR4, the interaction of FITC-labeled ubiquitin with CXCR4 was assessed by measuring the fluorescence associated with human monocyte cells (THP-1) after treating CSB6B at various concentrations (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we tested the effect of CSB6B in the extracellular space. It has been explored that the extracellular ubiquitin binds to CXCR4 as a ligand and turns on CXCR4 signaling, which results in enhanced AKT expression, AKT phosphorylation, and metastasis [13,31]. In the ubiquitin-CXCR4 signaling process, it is known that hydrophobic residues of ubiquitin including Phe4 and Val70 directly bind CXCR4, and the C-terminal motif facilitates receptor activation [31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytokine properties of ISG15 are reminiscent of potential cytokine properties of ubiquitin and other ubiquitin-like proteins. Several studies have suggested that extracellular ubiquitins serve as immune modulator during infectious and noninfectious inflammation [14,15]. However, not many reports are available regarding other ubiquitin-like proteins.…”
mentioning
confidence: 99%
“…The receptors for SDF-1 are C-X-C receptor (CXCR)7 [1] and CXCR4, the latter of which only binds SDF-1 and ubiquitin [2]. CXCR7 possesses a tenfold higher affinity for SDF-1 than CXCR4 [1]; however, it is expressed at very low levels on T cells [3].…”
Section: Introductionmentioning
confidence: 99%